Exploring the benefits of industry and community engagement in hydrogeology teaching - Lucy Reading; Sabrina Catania (Hydrogeology Journal, 2026)
The role of industry engagement in hydrogeology education remains undervalued, despite its potential to enhance student learning and career readiness. Integrating both industry and community partnerships can increase student engagement, deepen students understanding of hydrogeological concepts and raise awareness of career opportunities, potentially improving graduate outcomes. This study evaluates the integration of such partnerships in the “Groundwater Systems” unit at the Queensland University of Technology (QUT), Brisbane, Australia. The approach involved collaborating with industry partners, revising assessment and progressively expanding opportunities for student–industry engagement. Surveys were conducted to evaluate the success of this engagement and to identify barriers limiting student participation. The groundwater unit now features semester-long industry interactions, including immersion in community-linked groundwater research projects as part of major assessments. The observed benefits of this include increased interest in the subject material and enhanced understanding of hydrogeology concepts and methods. Alumni participation as industry guest speakers further demonstrates the potential for sustained partnerships to enhance graduate outcomes.